Slight differences in community structure and biodiversity of fish associated to a Cymodocea nodosa meadow in a shallow CO2 vent - Mirasole A; Signa G; Gianguzza P; Bonaviri C; Mazzola A; Vizzini S (2018)
Naturally acidified environments are used to test ecological hypotheses about the effects of ocean acidification on complex communities. Here, we used a shallow Mediterranean CO2 vent to study the coastal fish assemblages associated to Cymodocea nodosa seagrass meadows, long-term exposed to high pCO2 / low pH conditions. In particular, by using underwater visual census method, we assessed the structure and the biodiversity of fish assemblages living in a low pH site and in two control sites, in two periods of the year featured by dissimilar seagrass structure. The aim of this study was to test the effect of different pH on fish assemblages mediated by the habitat-forming structural species C. nodosa. Contrary to expectations, fish assemblages exposed to acidified conditions did not reveal striking differences, both in the community structure and in biodiversity, compared with both controls. Furthermore, a general higher abundance of small-sized individuals was found in the low pH site. Spatial and temporal patterns indicated that these differences can not be addressed to C. nodosa meadow structure at different pH conditions. Moreover, current findings suggest that fish may exploit the vent area above all for its enhanced food resources, and that detrimental effects of acidification can be overcome by fish mobility, using the closer control area as a ‘recovery zone’. Therefore, although fish may be able to withstand the projected lowering of pH, indirect effects of acidification (i.e. food resources alteration) could exacerbate changes in fish assemblages.